Modeling Nanocarrier Transport Across a 3D In Vitro Human Blood-Brain-Barrier Microvasculature - Ling Lee, Sharon Wei (Adv Healthc Mater, 2020)
Polymer nanoparticles (NPs), due to their small size and surface functionalization potential has demonstrated effective drug transport across the blood-brain-barrier (BBB). Currently, the lack of in vitro BBB models that closely recapitulate the complex human brain microenvironment contributes to the high failure rate of neuro-pharmaceutical clinical trials. In this work, a previously established microfluidic 3D in vitro human BBB model, formed by the self-assembly of human induced pluripotent stem cell-derived endothelial cells, primary brain pericytes and astrocytes in tri-culture within 3D fibrin hydrogel was exploited to quantify polymer NP permeability, as a function of their size and surface chemistry. Microvasculature were perfused with commercially available 100 – 400 nm fluorescent polystyrene (PS) NPs, and newly-synthesized 100 nm rhodamine-labelled polyurethane (PU) NPs. Confocal images were taken at different timepoints and computationally analyzed to quantify fluorescence intensity inside/outside the microvasculature, to determine NP spatial distribution and permeability in 3D. Results showed similar permeability of PS and PU NPs, which increased after surface-functionalization with brain-associated ligand holo-transferrin. Compared to conventional transwell models, our method enabled rapid analysis of NP permeability in a physiologically-relevant human BBB set-up. Therefore, this work demonstrates a new methodology to preclinically assess NP ability to cross the human BBB.